Employee engagement and physical evidende toward customer satisfaction on Bank Rakyat Larkin Perdana - Azmi, Fadhlur Rahim (2011)
To be successful, the organizations must focus on customer needs and wants. The needs and wants will determine our quantity demanded of our products. When the customer demanded of our products, they will evaluate level of the satisfaction. The evaluation of satisfaction will happen during the transaction and after sale service. The customer satisfaction very important because many researchers were discovered that customer satisfaction can effect of our organizational profitability. Due to this, the customer satisfaction and customer dissatisfaction must be considered to maintain the existing customers, to attract new customers and potential customers. The factors that influencing the customer satisfaction very important to determine whether our organization achieved the level of customer satisfaction or otherwise. Therefore, customer satisfaction very important for an organizational successful. From the previous research, the researchers also discuss about important of employee engagement involvement of employee and the physical evidence (servicescape). Those two component was included in the extra three marketing mix. This component will influence the customer satisfaction. On this study want to examine whether both component give the changes of customer satisfaction on Bank Rakyat Larkin Perdana.